Nutritional assessment of athletes - Driskell, Judy A. (Judy Anne); Wolinsky, Ira. (Boca Raton, FL : CRC Press, 2011)
'Evaluating dietary intake, determining energy metabolism, and conducting other nutritional assessments are essential in understanding the relationships between diet, exercise, health, and physical performance, especially in athletes. Several methods exist, each with their own advantages and limitations. Extensively referenced and filled with numerous tables and figures, this timely book focuses on the nutritional assessment of both recreational and professional athletes, including children, adolescents, and adults. In one volume, it presents methods for all types of nutritional evaluations, including dietary, anthropometric, physical activity needs, biochemical, and clinical assessments'--Provided by publisher.
Chapter 1 Estimation of Food and Nutrient Intakes of Athletes / Robert J. Moffatt, Virginia B. Tomatis, Donna A. Harris, and Ashley M. Deetz -- Chapter 2 Evaluation of Nutrient Adequacy of Athletes' Diets / Nanna L. Meyer and Melina M. Manore -- Chapter 3 Physique Assessment of Athletes: Concepts, Methods, and Applications / Gary J. Slater, Helen T. O'Connor, and Fiona E. Pelly -- Chapter 4 Body Composition and Gender Differences in Performance / Peter R.J. Reaburn, Ben J. Dascombe, and Xanne Janse de Jonge -- Chapter 5 Laboratory Methods for Determining Energy Expenditure of Athletes / Robert G. McMurray -- Chapter 6 Field Assessment of Physical Activity and Energy Expenditure among Athletes / Nuala M. Byrne, Sarah P. Shultz, and Andrew P. Hills -- Chapter 7 Molecular Aspects of Physical Performance and Nutritional Assessment / Yousef I. Hassan and Janos Zempleni -- Chapter 8 Assessment of Lipid Status of Athletes / Richard B. Kreider, Jonathan M. Oliver, and Amy F. Bragg -- Chapter 9 Assessment of Protein Status of Athletes / Benjamin F. Miller and Matthew M. Robinson -- Chapter 10 Assessment of Vitamin Status of Athletes / Mark D. Haub, Helena B. L$1'XY(Bst, and Kelcie L. Hubach -- Chapter 11 Assessment of Mineral Status of Athletes / Henry C. Lukaski and Angus G. Scrimgeour -- Chapter 12 Assessment of Hydration of Athletes / Fiona E. Pelly, Gary J. Slater, and Tanya M. King -- Chapter 13 Clinical Assessment of Athletes / Khursheed N. Jeejeebhoy and Farida M. Jeejeebhoy.s
Includes bibliographical references and index.
Keywords: Athletes -- Nutrition